INTERNAL DRAINAGE OF SUBRETINAL FLUID DURING CHANDELIER-ASSISTED SCLERAL BUCKLING. Issue Volume 16:Issues 1(2022) (January 2022) - Ankamah, Emmanuel; Siemerink, Martin J.; Polkinghorne, Philip J.; Nolan, John M.; Ng, Eugene
Abstract : Purpose: To describe the surgical technique of internal drainage of subretinal fluid as an adjunct to chandelier-assisted scleral buckling for the repair of rhegmatogenous retinal detachment. Methods: The technique of internal drainage with a sharp needle or cannula through a trocar is described and shown in a Supplemental Digital Content 1 (see Video, http://links.lww.com/ICB/A87 ). Results: Three patients (3 eyes) underwent scleral buckling for rhegmatogenous retinal detachment repair. Subretinal fluid was drained using the internal drainage approach in all cases. All three patients had successful reattachment of retina with improvement in visual function. No complications were reported related to vitreous loss, retinal incarceration, or redetachment following primary surgery. Conclusion: Internal drainage of subretinal fluid during chandelier-assisted scleral buckling is a useful technique that can be considered for repairing rhegmatogenous retinal detachment. Abstract : Supplemental Digital Content is Available in the Text.Internal drainage of subretinal fluid is a useful surgical technique to supplement chandelier-assisted scleral buckling procedures. This article reports the technique and discusses the advantages, subtleties, and disadvantages of this procedure.